Perlindungan Aksesibilitas Hak Politik Bagi Penyandang Disabilitas - Firstnandiar Glica Aini Suniaprily; Muhammad Aziz Zaelani; Adhy Nugraha; Erika Marsha Helena; Aprian Noor Dwi Saputra (Journal of Innovative and Creativity, 2025)
Persons with disabilities are citizens who have the same rights as other citizens. One of the rights of persons with disabilities is political rights. Descriptive research method with literature study approach. Data from sources such as books, journals and scientific articles collected through documentation techniques, identification of discourse of books, journals, papers, online articles, magazines, newspapers, and other relevant literature related to political party rigts of persons with disabilities in Indonesia. The data analysis technique in this research is content analysis by organizing and categorizing data to obtain research results that will be used as conclusions. This can be seen in terms of political socialization and also political accessibility. So, the government must provide political rights for people with disabilities as it should.